Notes on the systematics of the orchid-bee genus Eulaema (Hymenoptera, Apidae) - Melo,Gabriel A. R. (2014)
Notes on the systematics of the orchid-bee genus Eulaema (Hymenoptera, Apidae). The classification of the genus Eulaema is modified in order to make it congruent with recent phylogenetic hypotheses based on molecular data. The speciosa group, containing E. peruviana, E. speciosa and related species, is removed from E. (Eulaema) and transferred to E. (Apeulaema). New morphological characters are presented to support the revised scope of the subgenera and their diagnostic features are revised. Six species groups are recognized herein: two in E. (Apeulaema) and four in E. (Eulaema). A list of valid species in each species group and an identification key to males of each of the subgenera and species groups are provided. Finally, an older overlooked designation of a type species for Eulaema is presented in the Appendix.